Envases vacíos de productos plaguicidas y su afectación al medio ambiente - Olvera Renella, Carlos Alberto (2023)
The present study work has been carried out in reference to empty pesticide containers. Regarding the introduction, it is analyzed that the empty containers of pesticide products and its affectation to the environment, meanwhile, it is necessary to indicate that these chemical products have their origin of their utility since the XIX century. In reference to the objective, to know the affectation to the environment originated by the empty containers of pesticide products. The methodology is based on a bibliographic-non-experimental type of research with a qualitative approach, in which a documentary analysis was carried out by gathering information from relevant and important sources. As for the results, it was determined that these containers contaminate the soil and water if an adequate handling and management process is not carried out, since a proportion of the product remains in these containers and these residues are highly toxic for water and soil; the remains of the chemicals that remain persist in the environment for a long period of time and contaminate all types of water and subway sources. In conclusion, it has been possible to know the impact of empty pesticide containers on the environment, where it was determined that they are sources of contamination because they can filter through the soil, thus causing degradation of the earth's surface.